TELAAH PEMBELAJARAN MAHASISWA TERHADAP PERAN BAHASA INDONESIA DI PERGURUAN TINGGI: STUDENT LEARNING ABOUT THE ROLE OF INDONESIAN LANGUAGE IN UNIVERSITY - Suryani Barimbing; Yunisa Oktavia (Asosiasi Ide Bahasa Kepri, 2022)
The Indonesian language course is one of the general subjects that must be taught at the tertiary level, either at the Diploma or Bachelor level. This rule of course has been stated in Article 35 paragraph 3 of Law number 12 of 2002 which is related to learning in higher education. Based on the article, the Indonesian language courses at the university level have changed their names, namely to become general compulsory subjects (MKWU) which were originally called the General Basic Courses (MKDU). It can be said that a substance in the study of Indonesian general courses will always focus on an emphasis on skills in the use of Indonesian as a language known as the national language. However, in accordance with the existing truth, in doing academic writing which is an effort that can be made in obtaining a national literacy program as has happened at this time which is really not in accordance with the intended expectations. Of course, in reality this will have an impact on students at the high school level who will enter the university level who will of course study Indonesian language courses. Seeing in the problems that will arise in the learning process, of course, it is very necessary, namely learning model that will begin to lead to how the ability of the student in carrying out recovery from an event that is in learning. Of course, the learning model as proposed is a guide from various sources by referring to the main points of a problem that will be faced, of course, by lecturers of the Indonesian General Course.